Advantages and Disadvantages of Signing a Comprehensive Economic and Trade Agreement (CETA) for the Еconomies of the EU and Canada - P. Yu. Baryshnikov (Мир новой экономики)
This article presents an analysis of the main provisions of the Comprehensive Economic and Trade Agreement (CETA) signed by the government of Canada and the European Parliament at the end of 2016. In particular, the author analysed such aspects of the agreement as the abolition of customs tariffs, the introduction of common quality standards, access to the procurement market, modification of the system of investment disputes, etc. According to the results of the study, there was a mixed effect of the agreement for both Canada and the EU. For some sectors of the economies of the participating countries, the implementation of the CETA promises to create exceptional conditions for development, while for others the signing of a multilateral agreement is unprofitable or means losses. It should be noted that at the present stage the pros and cons of the СЕТА can be considered only at the theoretical level. It will be possible to draw objective conclusions about the impact of the multilateral trade agreement on the development of trade and economic relations between the countries only a certain time later after the ratification of the agreement by all parties. At the current stage of development of Canada-EU relations within the framework of the СЕТА, it can be noted that only the dynamic development and further improvement of the mechanisms of the multilateral agreement will make a trade and economic relations between the countries more open and transparent.